UV type coating material as well as preparation method and application thereof
By using UV coating materials, the problem of insufficient bending performance of existing ultra-thin glass at high and low temperatures is solved, good adhesion to the glass, water resistance and high and low temperature resistance are achieved, and the process is simplified.
Patent Information
- Application Number
- CN202310893651.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-21
AI Technical Summary
The ultra-thin glass used in existing folding screen mobile phones is insufficient when bending at high and low temperatures, and the thermosetting resin coating has a large shrinkage rate and slow curing speed, which is easy to be contaminated by dust in the environment and equipment, resulting in poor appearance. .
UV -type coating film material, which is composed of acrylic hydroxyl -butyl ester, hexal methylisocyanate, low TG single -sensitive UV monomer, low TG dual -level UV monomer, low TG polyurethane acrylic, and photistide. Fast solidification and low contraction rate are achieved through optical curing technology.
It achieves good adhesion to glass, water resistance and high and low temperature resistance, and is non-pressure sensitive and non-sticky to the touch after curing, simplifying the process.
Smart Images

Figure BDA0004355547170000091 
Figure BDA0004355547170000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ultra-thin glass processing materials, and specifically relates to a UV type coating material and a preparation method and application thereof. Background Art
[0002] In the fourth quarter of 2022, China's single-quarter shipments of foldable screen products hit a new high, with shipments exceeding 1.1 million units. The annual shipments were nearly 3.3 million units, a year-on-year increase of 118%, which was higher than expected. The share of foldable screen products in the domestic smartphone market has increased from 0.5% in 2021 to 1.2%. It is expected that in 2023, the global foldable screen market will increase by 52% year-on-year to 22.7 million units. Against this background, major smartphone manufacturers have launched foldable screen phones at a rate of one to two models a year.
[0003] At present, the cover plates used in foldable screen mobile phones are mostly film materials and flexible foldable ultra-thin glass (UTG, UltraThin Glass). The film material will have obvious creases after being folded for a certain period of time. Although the flexible foldable ultra-thin glass has excellent bending resistance, it is too thin and has poor impact resistance and explosion resistance. There are currently two solutions to solve the above performance defects: one is to coat one or more layers of flexible resin material on the surface of UTG. The flexible resin material can not only protect the ultra-thin glass well, but also has no effect on the bending performance; the other is center foldable ultra-thin glass (CFG, CenterFoldable Glass), that is, the thickness of the glass in the middle bending area is only 30-50μm, and the thickness of the non-bending area is 70-200μm.
[0004] Since the middle part of CFG has the property of being able to bend, there is a groove design in the middle part. The existence of the groove prevents CFG from being directly attached to the display panel, and the groove needs to be filled with a flexible resin material. Thermosetting resin coatings often contain solvents, and the dry film formed shrinks a lot, making it difficult to fill the groove. In addition, the curing speed of thermosetting materials is slow, and they are easily contaminated by dust in the environment and equipment during the curing process, resulting in poor appearance. The light-curing coating with 100% active ingredients has a fast curing speed, and the shrinkage rate of the film is much lower than that of thermosetting materials. However, coating on the surface of CFG not only requires the shrinkage rate and curing speed of the material, but also has special requirements for its performance. Because it needs to adapt to bending at high and low temperatures, the glass transition temperature (Tg) of the material is required to be lower than -20°C, and the material needs to be firmly attached to the glass substrate, so the material needs to have good adhesion. When Tg is low, the cured film layer is often pressure-sensitive, and dust particles are easy to adhere to the surface of the film layer and cannot be wiped clean, so the material cannot be pressure-sensitive. Since the application scenario is electronic products, there is a need for waterproofing, and good water resistance is required. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a UV type coating material and its preparation method and application. The UV type coating material of the present invention has a low glass phase transition temperature, good adhesion to glass, good water resistance, no pressure sensitivity, no stickiness to the touch after curing, and excellent high and low temperature resistance.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] On the one hand, the present invention provides a UV type coating material, and the raw materials for preparing the UV type coating material include the following components: hydroxybutyl acrylate, hexamethylene diisocyanate extended by 1,5-pentanediol or 1,4-butanediol, a low Tg monofunctional UV monomer, a low Tg difunctional or higher UV monomer, a low Tg polyurethane acrylate and a photoinitiator.
[0008] The UV coating material obtained by reacting the raw materials prepared as above in the present invention can have a low glass phase transition temperature, good adhesion to glass, good water resistance, no pressure sensitivity, no stickiness to the touch after curing, and excellent high and low temperature resistance.
[0009] UV materials with low Tg points are often unbranched long-chain molecular structures with poor adhesion, while the hydroxypropyl acrylate in the present invention is also an unbranched long-chain molecular structure, but the end of the molecule has a strong polar group to enhance the adhesion of the film layer. The addition of low Tg monomers and resins can further reduce the Tg point of the material, and the monomers are fast-reacting, which can make the material have a higher degree of curing during curing and make the material non-pressure sensitive.
[0010] In the present invention, the hydroxybutyl acrylate has a low Tg point and contains hydroxyl groups, and can be reacted with isocyanate to obtain an acrylate prepolymer with a low Tg point. The free hydroxybutyl acrylate or the excess hydroxyl groups can provide the material with adhesion on glass.
[0011] In the present invention, the hexamethylene diisocyanate chain-extended by 1,5-pentanediol or 1,4-butanediol has a very low Tg point and can react with hydroxybutyl acrylate to generate an acrylate prepolymer with a very low Tg point.
[0012] In the present invention, the low Tg monofunctional UV monomer can dilute the synthesized acrylate prepolymer to adjust the viscosity of the material.
[0013] In the present invention, the low Tg bifunctional UV monomer can also play a role in adjusting the viscosity of the material, and at the same time play a role in making the material react quickly and not sticky to the touch.
[0014] In the present invention, the low Tg polyurethane acrylate can play a role in adjusting the Tg point and viscosity.
[0015] In the present invention, the photoinitiator enables the material to polymerize under UV light environment.
[0016] Preferably, the low Tg monofunctional UV monomer is a fast-reacting low Tg monofunctional monomer selected from any one of ethoxyethoxyethyl acrylate, isodecyl acrylate, isooctyl acrylate, hydroxybutyl acrylate, isononyl acrylate, lauric acid methacrylate, 2-(2-ethoxyethoxy)ethyl acrylate, tridecyl acrylate or caprolactone acrylate, or a combination of at least two thereof.
[0017] Preferably, the low Tg bifunctional or higher UV monomer includes a low Tg bifunctional UV monomer or a low Tg trifunctional UV monomer.
[0018] Preferably, the low Tg bifunctional or higher UV monomer comprises alkoxylated hexanediol diacrylate and / or ethoxylated trimethylolpropane triacrylate.
[0019] Preferably, the raw materials for preparing the UV type coating material also include a catalyst.
[0020] Preferably, the catalyst comprises any one of dibutyltin dilaurate, stannous octoate or organic bismuth, or a combination of at least two thereof.
[0021] Preferably, the photoinitiator comprises one or a combination of at least two of 1-hydroxy-cyclohexyl-1-phenyl ketone, 2,4,6-(trimethylbenzoyl)diphenylphosphine oxide, 2-hydroxy-2-methyl-1-phenyl-propanone or phenylbis(4,4,6-trimethylbenzoyl)phosphine oxide.
[0022] Preferably, the photoinitiator further includes a thiol photoinitiator containing a thiol group.
[0023] Preferably, in the raw materials for preparing the UV type coating material, hydroxybutyl acrylate and hexamethylene diisocyanate chain-extended with 1,5-pentanediol or 1,4-butanediol form an acrylate prepolymer.
[0024] The acrylate prepolymer of the present invention has not only a low Tg point, good glass adhesion and water resistance, but also rapid reaction.
[0025] Preferably, the weight ratio of hydroxybutyl acrylate to hexamethylene diisocyanate extended by 1,5-pentanediol or 1,4-butanediol is 38:22-33. If the amount of hydroxybutyl acrylate is too much, it will lead to incomplete polymerization, excessive oxygen inhibition, and sticky touch. If the amount of hydroxybutyl acrylate is too little, it will increase Tg and easily break when bent at low temperature.
[0026] Preferably, in the preparation raw materials, the weight percentage of the acrylate prepolymer is 60-85%, for example, 60%, 65%, 68%, 70%, 75%, 78%, 80%, or 85%.
[0027] Preferably, in the preparation raw material, the weight percentage of the low Tg monofunctional UV monomer is 10-30%, for example, 10%, 13%, 15%, 18%, 20%, 23%, 25%, 28% or 30%.
[0028] Preferably, in the preparation raw material, the weight percentage of the low Tg bifunctional or higher UV monomer is 0-20%, for example 0%, 1%, 3%, 5%, 8%, 10%, 13%, 15%, 18% or 20%.
[0029] Preferably, in the preparation raw materials, the weight percentage of the low Tg polyurethane acrylate is 0-10%, for example, 0%, 1%, 3%, 5%, 8% or 10%.
[0030] Preferably, the catalyst is used in an amount of 0.03%-0.1% of the total weight of hydroxybutyl acrylate and hexamethylene diisocyanate extended by 1,5-pentanediol or 1,4-butanediol, for example 0.03%, 0.05%, 0.08% or 0.1%.
[0031] Preferably, in the preparation raw materials, the weight percentage of the initiator is 2-7%, for example, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5% or 7%.
[0032] In the present invention, the low Tg in the low Tg monofunctional UV monomer, the low Tg difunctional or higher UV monomer and the low Tg polyurethane acrylate refers to a Tg lower than -40°C.
[0033] On the other hand, the present invention provides a method for preparing the UV type coating material as described above, the preparation method comprising the following steps:
[0034] (1) Hydroxybutyl acrylate reacts with hexamethylene diisocyanate chain-extended with 1,5-pentanediol or 1,4-butanediol to obtain an acrylate prepolymer;
[0035] (2) Adding a low Tg monofunctional UV monomer, a low Tg difunctional or higher UV monomer, a low Tg polyurethane acrylate and a photoinitiator to the reactant of step (1), mixing, and obtaining the UV type coating material.
[0036] Preferably, the reaction in step (1) is carried out in the presence of a catalyst.
[0037] Preferably, the catalyst comprises dibutyltin dilaurate.
[0038] Preferably, the reaction temperature in step (1) is 70-110°C (e.g., 70°C, 73°C, 75°C, 78°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C or 110°C), and the reaction time is 2-4 hours (e.g., 2 hours, 2.5 hours, 2.8 hours, 3 hours, 3.5 hours, 3.8 hours or 4 hours).
[0039] Preferably, the viscosity of the UV coating material is 200-500 cps, for example, 200 cps, 250 cps, 300 cps, 350 cps, 400 cps, 450 cps or 500 cps.
[0040] On the other hand, the present invention provides the use of the UV type coating material as described above as a coating material for ultra-thin glass of unequal thickness.
[0041] On the other hand, the present invention provides a non-uniform thickness ultra-thin glass, which includes a foldable non-uniform thickness ultra-thin glass and a coating covering the surface of the foldable non-uniform thickness ultra-thin glass, wherein the coating is obtained by curing the UV type coating material as described above.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] The UV coating material described in the present invention uses all resins and monomers with low Tg points. The Tg point of the material is very low, and its cured product can be bent at low temperatures; it has 100% solid components and a very low shrinkage rate, and is suitable for CFG coating. The prepolymer synthesized using hydroxybutyl acrylate not only has a very low Tg point, but also has good adhesion to glass due to the presence of polar groups, does not require a primer, and reduces the process difficulty. Fast-reacting monomers and resins are used, the curing speed is fast, the cross-linking is relatively complete, and the material is non-pressure sensitive. DETAILED DESCRIPTION
[0044] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0045] The raw materials described in the present invention can all be purchased in the domestic chemical market.
[0046] HDI chain extension reaction:
[0047] (1) Preparation of HDI via 1,5-pentanediol:
[0048] 84 parts by weight of HDI (hexamethylene diisocyanate) were added to a sealed container equipped with a condensation reflux device, stirred at a speed of 1000 RPM, heated to 60°C, 45 parts by weight of 1,5-pentanediol were added to the container at a rate of 3 g / min, and reacted for 80 minutes to obtain the final product.
[0049] (2) Preparation of HDI with 1,4-butanediol chain extension
[0050] 84 parts by weight of HDI (hexamethylene diisocyanate) were added to a sealed container equipped with a condensation reflux device, stirred at a speed of 1300 RPM, heated to 70°C, 45 parts by weight of 1,4-butanediol were added to the container at a rate of 5 g / min, and reacted for 100 minutes to obtain the final product.
[0051] Example 1
[0052] This embodiment provides a UV type coating material, and the preparation method thereof comprises the following steps:
[0053] 38 parts by weight of hydroxybutyl acrylate, 33 parts by weight of HDI extended by 1,5-pentanediol and 0.03 parts by weight of dibutyltin dilaurate were added to a reaction vessel equipped with a condensation reflux device, stirred and heated to 90°C, and reacted for 3 hours to obtain a difunctional acrylate prepolymer. The above acrylate prepolymer has not only a low Tg point (-45°C), good adhesion to glass (GB / T9286-1998 paint film adhesion test standard, 5B), good water resistance (paint film adhesion test after boiling at 85°C / 1h, >4B), but also rapid reaction (360mW / cm 2 , 3000mJ / cm 2 70% (by weight) of the above acrylate prepolymer, 27% of ethoxyethoxyethyl acrylate, 1.5% of 1-hydroxy-cyclohexyl-1-phenyl ketone, and 1.5% of 2,4,6-(trimethylbenzoyl)diphenylphosphine oxide were added into a container and stirred evenly to obtain a material with a viscosity of about 320 cps.
[0054] Example 2
[0055] This embodiment provides a UV type coating material, and the preparation method thereof comprises the following steps:
[0056] 38 parts of hydroxybutyl acrylate, 22 parts of HDI extended by 1,4-butanediol and 0.03 parts of dibutyltin dilaurate were added to a reaction vessel equipped with a condensation reflux device, stirred and heated to 110°C, and reacted for 2 hours to obtain a trifunctional acrylate prepolymer. The above acrylate prepolymer has not only a low Tg point (-52°C), good adhesion to glass (GB / T9286-1998 paint film adhesion test standard, 5B), good water resistance (paint film adhesion test after boiling at 85°C / 1h, >4B), but also rapid reaction (360mW / cm 2 ,3000mJ / cm 2 70% of the above acrylate prepolymer, 20% of 2-(2-ethoxyethoxy)ethyl acrylate, 5% of alkoxylated hexanediol diacrylate, 2.5% of 1-hydroxy-cyclohexyl-1-phenyl ketone, and 2.5% of 2,4,6-(trimethylbenzoyl)diphenylphosphine oxide were added into a container and stirred to obtain a material with a viscosity of about 260 cps.
[0057] Example 3
[0058] This embodiment provides a UV type coating material, and the preparation method thereof comprises the following steps:
[0059] 38 parts by weight of hydroxybutyl acrylate, 33 parts by weight of HDI extended by 1,5-pentanediol and 0.05 parts by weight of dibutyltin dilaurate were added to a reaction vessel equipped with a condensation reflux device, stirred and heated to 70°C, and reacted for 4 hours to obtain a trifunctional acrylate prepolymer. The above acrylate prepolymer has not only a low Tg point (-45°C), good adhesion to glass (GB / T9286-1998 paint film adhesion test standard, 5B), good water resistance (paint film adhesion test after boiling at 85°C / 1h, >4B), but also rapid reaction (360mW / cm 2 ,3000mJ / cm 2 60% of the above acrylate prepolymer, 20% of 2 (2-ethoxyethoxy) ethyl acrylate, 10% of alkoxylated hexanediol diacrylate, 5% of low Tg polyurethane acrylate, 2.5% of 1-hydroxy-cyclohexyl-1-phenyl ketone, and 2.5% of 2,4,6-(trimethylbenzoyl) diphenylphosphine oxide were added into a container and stirred to obtain a material with a viscosity of 240 cps.
[0060] Example 4
[0061] This embodiment provides a UV type coating material, and the preparation method thereof comprises the following steps:
[0062] 38 parts by weight of hydroxybutyl acrylate, 33 parts by weight of HDI extended with 1,5-pentanediol and 0.03 parts by weight of dibutyltin dilaurate were added to a reaction vessel equipped with a condensation reflux device, stirred and heated to 90°C, and reacted for 3 hours to obtain a trifunctional acrylate prepolymer. The above acrylate prepolymer not only has a low Tg point (-45°C), good adhesion to glass (GB / T9286-1998 paint film adhesion test standard, 5B), good water resistance (paint film adhesion test after boiling at 85°C / 1h, >4B), but also reacts quickly (360mW / cm 2 ,3000mJ / cm 2 85% of the above acrylate prepolymer, 5% of ethoxyethoxyethyl acrylate, 5% of 2(2-ethoxyethoxy)ethyl acrylate, 1.5% of 1-hydroxy-cyclohexyl-1-phenyl ketone, 1.5% of 2,4,6-(trimethylbenzoyl)diphenylphosphine oxide and 2% of dodecyl mercaptan were added into a container and stirred evenly to obtain a material with a viscosity of about 440 cps.
[0063] Comparative Example 1
[0064] The only difference between this comparative example and Example 1 is that hydroxybutyl acrylate and hexamethylene diisocyanate do not react to produce a trimer.
[0065] That is, the preparation method comprises the following steps:
[0066] 38 parts by weight of hydroxybutyl acrylate, 33 parts by weight of HDI extended by 1,5-pentanediol and 0.03 parts by weight of dibutyltin dilaurate were added to a reaction vessel equipped with a condensation reflux device, and a mixture was obtained. 70% (weight percentage) of the above mixture, 27% ethoxyethoxyethyl acrylate, 1.5% of 1-hydroxy-cyclohexyl-1-phenyl ketone, and 1.5% of 2,4,6-(trimethylbenzoyl) diphenylphosphine oxide were added to the container, and the material with a viscosity of 10 cps was obtained by stirring evenly. Because it does not undergo polymerization reaction, the average molecular weight is small, so the viscosity is small; most of the HDI after chain extension fails to participate in the reaction and will exist as a liquid. During the photocuring process, the material will always be a liquid and cannot form a coating.
[0067] Comparative Example 2
[0068] The only difference between this comparative example and Example 3 is that all monomers in the material are low Tg bifunctional monomers.
[0069] That is, the preparation method comprises the following steps:
[0070] 38 parts by weight of hydroxybutyl acrylate, 33 parts by weight of HDI extended by 1,5-pentanediol and 0.05 parts by weight of dibutyltin dilaurate were added to a reaction vessel equipped with a condensation reflux device, and mixed at room temperature to obtain a mixture. 70% of the above mixture, 27% alkoxylated hexanediol diacrylate, 5% low Tg polyurethane acrylate, 2.5% 1-hydroxy-cyclohexyl-1-phenyl ketone, and 2.5% 2,4,6-(trimethylbenzoyl) diphenylphosphine oxide were added to the container, and the viscosity was about 350cps. Because the monomers of the material are all difunctional monomers, the hardness of the material is relatively large and the finished paint film is easy to break when bent.
[0071] The material performance test results of Examples 1-4 and Comparative Examples 1-2 are shown in Table 1.
[0072] Table 1
[0073]
[0074]
[0075] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the UV type coating material and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A UV coating material, characterized in that: The raw materials for preparing the UV type coating material include the following components: hydroxybutyl acrylate, hexamethylene diisocyanate extended by 1,5-pentanediol or 1,4-butanediol, low Tg monofunctional UV monomer, low Tg bifunctional or higher UV monomer, low Tg polyurethane acrylate and photoinitiator.
2. The UV type coating material according to claim 1, characterized in that: The low Tg monofunctional UV monomer is a fast-reacting low Tg monofunctional monomer selected from any one of ethoxyethoxyethyl acrylate, isodecyl acrylate, isooctyl acrylate, hydroxybutyl acrylate, isononyl acrylate, lauric acid methacrylate, 2-(2-ethoxyethoxy)ethyl acrylate, tridecyl acrylate or caprolactone acrylate, or a combination of at least two thereof.
3. The UV type coating material according to claim 1 or 2, characterized in that: The low Tg bifunctional or higher UV monomer includes a low Tg bifunctional UV monomer or a low Tg trifunctional UV monomer; Preferably, the low Tg bifunctional or higher UV monomer comprises alkoxylated hexanediol diacrylate and / or ethoxylated trimethylolpropane triacrylate; Preferably, the raw materials for preparing the UV type coating material further include a catalyst; Preferably, the catalyst comprises any one of dibutyltin dilaurate, stannous octoate or organic bismuth, or a combination of at least two thereof. Preferably, the photoinitiator comprises one or a combination of at least two of 1-hydroxy-cyclohexyl-1-phenyl ketone, 2,4,6-(trimethylbenzoyl)diphenylphosphine oxide, 2-hydroxy-2-methyl-1-phenyl-acetone or phenylbis(4,4,6-trimethylbenzoyl)phosphine oxide; Preferably, the photoinitiator further includes a thiol photoinitiator containing a thiol group.
4. The UV type coating material according to any one of claims 1 to 3, characterized in that: The raw materials for preparing the UV type coating material include hydroxybutyl acrylate and hexamethylene diisocyanate chain-extended by 1,5-pentanediol or 1,4-butanediol to form an acrylate prepolymer; Preferably, the weight ratio of the hydroxybutyl acrylate to the hexamethylene diisocyanate chain-extended with 1,5-pentanediol or 1,4-butanediol is 38:22-33.
5. The UV type coating material according to any one of claims 1 to 4, characterized in that: In the raw materials for preparation, the weight percentage of the acrylic ester prepolymer is 60-85%; Preferably, in the preparation raw materials, the weight percentage of the low Tg monofunctional UV monomer is 10-30%; Preferably, in the preparation raw materials, the weight percentage of the low Tg bifunctional or higher UV monomer is 0-20%; Preferably, in the preparation raw materials, the weight percentage of the low Tg polyurethane acrylate is 0-10%; Preferably, the catalyst is used in an amount of 0.03% to 0.1% of the total weight of hydroxybutyl acrylate and hexamethylene diisocyanate chain-extended with 1,5-pentanediol or 1,4-butanediol.
6. The UV type coating material according to any one of claims 1 to 5, characterized in that: In the preparation raw materials, the weight percentage of the initiator is 2-7%.
7. The method for preparing a UV type coating material according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) Hydroxybutyl acrylate reacts with hexamethylene diisocyanate chain-extended with 1,5-pentanediol or 1,4-butanediol to obtain an acrylate prepolymer; (2) Adding a low Tg monofunctional UV monomer, a low Tg difunctional or higher UV monomer, a low Tg polyurethane acrylate and a photoinitiator to the reactant of step (1), mixing, and obtaining the UV type coating material.
8. The preparation method according to claim 7, characterized in that: The reaction in step (1) is carried out in the presence of a catalyst; Preferably, the catalyst comprises dibutyltin dilaurate; Preferably, the reaction temperature in step (1) is 70-110° C., and the reaction time is 2-4 hours; Preferably, the viscosity of the UV type coating material is 200-500 cps.
9. Use of the UV type coating material according to any one of claims 1 to 6 as a non-uniform thickness ultra-thin glass coating material.
10. An ultra-thin glass with non-uniform thickness, characterized in that: The non-uniform thickness ultra-thin glass comprises a foldable non-uniform thickness ultra-thin glass and a coating covering the surface of the foldable non-uniform thickness ultra-thin glass, wherein the coating is obtained by curing the UV coating material according to any one of claims 1 to 6.
Citation Information
Patent Citations
Preparation method and applications of low Tg polyurethane acrylate prepolymer
CN108341922A
Flexible UV photocureable coating, and preparation method and application thereof
CN111138966A
High-adhesion toughened priming coat for transparent PI substrate
CN111732866A
Coated Optical Articles
US20220186065A1